Formation of Complexes of f-Elements with Electron-Withdrawing N-Heterocyclic Diamides: Extraction and Solution Photophysics - Nataliya E. Borisova; Anastasiia V. Kharcheva; Kirill D. Shmelkov; Mikhail A. Gerasimov; Mariia V. Evsiunina; Petr I. Matveev; Alexey V. Ivanov; Yulia G. Sokolovskaya; Svetlana V. Patsaeva (Metals, 2023)
To examine the scope of the abnormal aryl strengthening effect (an increase in the extraction of metal ions when an aromatic substituent is introduced into the amide group) on f-metal extraction, a series of tetradentate diamide-type extragents bearing electron-withdrawing pyridine rings in amide moieties of the molecules were tested. The solvent extraction of Am(III)/Eu(III) pairs was investigated under various conditions, the solution chemistry of the lanthanide-extragents systems was studied, and the bonding constants were calculated for complexes of Eu(III) and Tb(III) ions with diamides. The photophysical properties of chemically synthesized ligand/metal (LM) complexes with various LM compositions were additionally studied in depth. The replacement of a phenyl ring by a pyridine one led to a critical reduction in metal affinity, showing the major contribution of electronic nature to the abnormal aryl strengthening effect. However, the pyridine group in the amide side chain provided additional coordination positions for metal ion binding; corresponding complexes with LM2 composition were detected in the system and their stability was calculated. Due to the low stability of the corresponding LM2 complexes, chemical synthesis of the complexes led to the formation of only one metal-containing species with LM composition. The luminescence spectra of europium and terbium complexes of the LM composition were studied. Differences were discovered in the luminescence excitation spectra of europium and terbium complexes with the same ligand. The luminescence quantum yields and luminescence lifetimes of solutions of europium and terbium complexes were determined.